Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahan - Selsa Kurniawati Putri; Muslichah Muslichah (ITB AAS INDONESIA, 2023)
The purpose of this study was to examine the effect of profitability and leverage on firm value. The population of this research is the food and beverage sector companies which are listed on the IDX for 2019-2021, totaling 72 companies. By using purposive sampling, the samples used in this study were 26 companies and 78 observational data. The results showed that profitability has an effect on firm value, but leverage has no effect on firm value. The results of this study provide an overview to investors regarding the value of the company so that it can be used as a guide before making an investment. Furthermore, the results of this study also provide an overview for the company regarding the variables that need to be the focus of the company so that the firm's value can be increased.